PARKING DEMAND ANALYSIS OF REST AND SERVICE AREA ALONG EXPRESSWAY IN SOUTHERN REGION, JOHOR MALAYSIA (Malaysian Journal of Civil Engineering, 2018)
Rest and Service Area (RSA) is an important aspect in highway operation in terms of safety and comfort for highway users. Stopping and resting at these facilities will help reducing users fatigue and thus avoiding possible accidents. Existing guidelines for RSA planning apparently provides insufficient information on the design capacity for estimating parking requirements for RSA. The objectives of this study were to determine the parking demand trend on RSA, and to evaluate significant parameters related to parking demand. This study was conducted on six RSA located in southern region of Peninsular Malaysia, Johor. Variations of traffic volume on major road and the size of the facilities on RSA were observed on two days for 10 hours for each site. Correlation analyses were conducted to determine the relationship of these two parameters as related to parking demand on RSA. It was found that the parking demand varies with time of the day and day of week. The analysis showed that there is a significant correlation between vehicular volume on major road and gross floor area to parking demand on RSA. Linear regression models were developed to predict parking demand on the RSA land use type. The developed models equations are recommended to be used for RSA land use type.